Needs Analysis on the Improvement of English for Informatics Courses Based on the Perception of Non-English Teachers of the IT Department of State Polytechnic of Malang - Atiqah Nurul Asri,Farida Ulfa,Satrio Binusa Suryadi (International Conference on Industrial Revolution for Polytechnic Education, 2019)
English language teaching in IT Department is treated as English for Specific Purposes (ESP) where English is taught within IT contexts. Therefore, English language course in this department are under such names as English for Informatics courses. In teaching them, mastering the four language skills and also having ample knowledge on grammar and vocabulary possibly are not adequate the ESP teachers. The technical terminologies and the context of the materials used in the classroom may be challenges for them as well. Moreover, they need to ensure the students’ specific needs achieved and they will be prepared for their future employment. As technical and vocational education and training is practiced at State Polytechnic of Malang where the main goal is preparing students with knowledge and skills for the world of work, the available ESP teachers have been aware and adjusted the materials to suit the students’ needs. The awareness in understanding the students’ needs is significant since it is a way to determine the proposition on whether or not the courses, materials%2